Efek ekstrak etanol biji alpukat (persea americana) terhadap biofilm candida albicans - Selviana Wulansari; Dhea Fatharani Mintarjo (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Candida albicans is the most common bacteria related to root canal treatment failure. Avocado seeds (Persea americana) contain terpenoids, alkaloids, flavonoids, steroids, saponins and tannins that have antibacterial activity. Purpose: To determine the effect of avocado seed ethanol extract on C.albicans biofilm. Methods: The effect of avocado seed ethanol extract on C.albicans ATCC 10231 biofilm was evaluated by crystal violet assay. C.albicans were inoculated into Sabouraud Dextrose Broth at 37C for 24 h. A volume of 200 L (108 CFU/mL) C.albicans culture were distributed into 96-well plates and incubated for 24 h. Avocado seed ethanol extract was diluted into 6 concentrations: 100%, 50%, 25%, 12.5%, 6.25% and 3.13% with NaOH 0.1N. NaOCl 5.25% was used as positive control. The extract were added into 96-well plates with C.albicans culture and incubated for 1 h, 3 h and 24 h. The biofilm biomass was calculated by 0,5% crystal violet staining and the optical density value was measured using a microplate reader (490 nm). Results: Ethanol extract of avocado seeds of all concentrations from each incubation period had an antibiofilm against C.albicans when compared to negative control (p < 0.05). The concentration of the extract that has the highest antibiofilm is 6.25% with an incubation period of 24 h which showed an optical density value of 0.011 ± 0.024. Conclusion: Avocado seed ethanol extract has antibiofilm against C.albicans.